2014
DOI: 10.1152/jn.00475.2013
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary and involuntary running in the rat show different patterns of theta rhythm, physical activity, and heart rate

Abstract: CC. Voluntary and involuntary running in the rat show different patterns of theta rhythm, physical activity, and heart rate. J Neurophysiol 111: 2061-2070, 2014. First published March 12, 2014 doi:10.1152/jn.00475.2013.-Involuntarily exercising rats undergo more physical and mental stress than voluntarily exercising rats; however, these findings still lack electrophysiological evidence. Many studies have reported that theta rhythm appears when there is mental stress and that it is affected by emotional status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…In contrast, rodent studies employing therapeutic exercise uniformly show robust analgesic effects in a variety of persistent pain models and using a variety of exercise intensities [4; 9; 11; 1824; 34; 35; 41; 54; 63; 69; 81; 82; 93; 102; 103; 112; 132]. Importantly, none of these studies assessed stress-related outcomes such as plasma corticosterone despite employing forced running paradigms that can be highly stressful [28; 36; 48; 62; 74; 80; 88; 89; 92]. As such, while carefully conditioned forced running paradigms can activate reward centers in the rodent brain [52] and can result in beneficial physiological changes in certain contexts [51; 64; 92; 94], it is nonetheless difficult to determine if the observed analgesic effects were, at least in part, mediated by stress-induced analgesic mechanisms [15; 68].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, rodent studies employing therapeutic exercise uniformly show robust analgesic effects in a variety of persistent pain models and using a variety of exercise intensities [4; 9; 11; 1824; 34; 35; 41; 54; 63; 69; 81; 82; 93; 102; 103; 112; 132]. Importantly, none of these studies assessed stress-related outcomes such as plasma corticosterone despite employing forced running paradigms that can be highly stressful [28; 36; 48; 62; 74; 80; 88; 89; 92]. As such, while carefully conditioned forced running paradigms can activate reward centers in the rodent brain [52] and can result in beneficial physiological changes in certain contexts [51; 64; 92; 94], it is nonetheless difficult to determine if the observed analgesic effects were, at least in part, mediated by stress-induced analgesic mechanisms [15; 68].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that relatively gentle exercise for C57BL/6 mice without electrical stimulation during treadmill running with voluntary walking speed may prevent contamination of experimental data 23 . In addition, rats with forced-treadmill exercise have shown more complicated theta wave in the brain and heart rate than rats with voluntary exercise rats 25 . Therefore, we used a voluntary exercise device in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zhang and colleagues recently found that locomotion drives cortex-wide increases in blood oxygenation and that this effect is mediated by respiration 43 . These studies rely on the use of treadmills or similar setups which generate different patterns of electrical activity than the ones observed in natural movement, possibly because of the discrepancies between vestibular and visual sensory inputs 44 . During locomotion, we found strong activations in multiple brain regions, some of which might be associated with sensory stimulation (dorsal thalamus), spatial information (dorsal hippocampus, retrosplenial cortex), motor control (hypothalamus) or reward uptake (Po, VPM, striatum).…”
Section: Discussionmentioning
confidence: 99%